2015
DOI: 10.4238/2015.july.27.4
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian inheritance, genetic linkage, and genotypic disequilibrium at microsatellite loci in Genipa americana L. (Rubiaceae)

Abstract: ABSTRACT. Genipa americana is a tropical tree species that is widely distributed in the humid tropical and subtropical regions of Central and South America. This study investigated Mendelian inheritance, genetic linkage, and genotypic disequilibrium at six microsatellite loci developed for G. americana. Adult trees (188) and regenerants (163) were sampled and genotyped in a fragmented population of the species. We also genotyped open-pollinated seeds from 12 seed-trees during reproductive events in 2010 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 8 publications
0
13
0
1
Order By: Relevance
“…Carneiro et al (2012) observed deviations from the expected 1:1 segregation only in locus HC33 (the same locus as used in the present study) in H. courbaril. Tambarussi et al (2013) observed deviations from the expected 1:1 segregation in 3.7% of the tests in Cariniana legalis, and Manoel et al (2015) observed deviations from the expected segregation of 1:1 in 29% of tests in Genipa americana.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Carneiro et al (2012) observed deviations from the expected 1:1 segregation only in locus HC33 (the same locus as used in the present study) in H. courbaril. Tambarussi et al (2013) observed deviations from the expected 1:1 segregation in 3.7% of the tests in Cariniana legalis, and Manoel et al (2015) observed deviations from the expected segregation of 1:1 in 29% of tests in Genipa americana.…”
Section: Discussionmentioning
confidence: 85%
“…The HC14 locus stands out for showing significant linkage in 14 of 54 cases (25.9%). These linkages between pairs of loci found in several progenies may be a true genetic linkage, or it may be caused by deviations from a 1:1 Mendelian segregation (Manoel et al, 2015). We propose that it is the latter because 11 of the 14 significant linkage tests involving locus HC14 were detected in families that also showed significant segregation deviation.…”
Section: Discussionmentioning
confidence: 87%
“…Thus, the genotypic disequilibrium that we detected may be attributed to genetic drift caused by forest fragmentation in the study region. Studies on other tree species have also found an absence of genetic linkage with a presence of genotypic disequilibrium, including Araucaria angustifolia (Medina-Macedo et al, 2014), Copaifera langsdorffii (Tarazi et al, 2010), Cariniana legalis (Tambarussi et al, 2013), and Genipa americana (Manoel et al, 2015). The nine microsatellite loci evaluated in this study exhibit Mendelian inheritance, are Continued on next page n 1 and n 2 are the sample size; G 1 and G 2 are the maximum likelihood G statistics for the hypothesis of n ij : n ii + n jj and n ik : n ik , respectively, for one degree of freedom.…”
Section: Discussionmentioning
confidence: 99%
“…However, in order to use molecular markers as genetic markers, it is important to determine whether their inheritance follows the rules of Mendelian segregation, and whether the loci are genetically linked (Tambarussi et al, 2013;Manoel et al, 2015;Moraes et al, 2016). Studies assessing linkage among loci are also necessary because the detected loci are used to calculate averages among loci in population genetic studies; therefore, linked loci can create bias in the estimates (Guidugli et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Significant values were observed for different families and occurred more frequently between the following pairs: EMBRA2xEMBRA3, EMBRA2xEMBRA63, and EMBRA204xEMBRA128. The significant linkage may be the result of true genetic linkage or deviations from 1:1 Mendelian segregation (Manoel et al, 2015;Moraes et al, 2015), as observed for EMBRA2 and EMBRA63. The absence of linkage between the loci is important concerning models used in population genetic analyses, which assume random segregation between alleles of different loci.…”
Section: Discussionmentioning
confidence: 99%